PROBLEMS OF TRANSLATING NAVOY'S LYRICS INTO FOREIGN LANGUAGES - Shermamatova (Journal of Learning on History and Social Sciences, 2024)
The article talks about the translations of Alisher Navoi's ghazals and rubai into English by Uzbek and foreign translators. Their achievements and shortcomings are thoroughly analyzed. Some suggestions and recommendations were given and relevant conclusions were drawn